Driving the Digital Transformation in a Tier 2 Company: Big Data Customer Central Product Management of a Vehicle Autonomous System Enterprise Architecture-Based - Kind-Trueller, Kathrin (Digital Repository of Theses, 2024)
This study evaluates how a Tier-2 company operating across the vehicle autonomous system industry can use blockchain-based QA strategies efficiently, particularly when managing large datasets for customer-centric product areas to focus effectively. The subject case-study company looks towards optimizing SW production workflows by embracing all benefits of blockchain technologies. Namely a strategic approach intent on improving enterprise architecture - eventually improving the autonomous vehicle system efficiency resulting in more informed decision-making processes and justifiable allocation of resources. At the same time researching through mixed methods if such a system improved the product quality, for this both the managers of such Tier-2 companies were interviewed, and as well as potential customers were surveyed. vii The researcher interviewed managers of Tier-2 companies in Germany, and within the United States, surveyed potential customers and evaluated their perceptions, experiences, and attitudes towards integrating blockchain technology for QA purposes. The findings uncovered valuable insights into potential impacts resulting from driving digital transformations enabled by this technology when implemented with QA effectively in this industry sector's customer-centric product management-specific areas. Attitudes among managers towards applying blockchain-based QA strategies remain positive due to benefits, such as ensuring data integrity, security, and other trustworthiness features throughout the software development process. Potential customers expressed interest in having blockchain technology integrated within their autonomous vehicle systems because of the confidence instilled - deriving from reliable performance backed up by verifiable secure data. It was found that automation enabled through improved verification processes by using blockchain technologies along the SW lifecycle, may provide greater efficiency levels while reducing manual intervention instances effectively, providing simplified product management unencumbered by a wide range of data sources, that can be trusted while optimising decisions with accessible resource allocation programs. Within the survey process were several challenges and limitations encountered regarding Blockchain technology implementation. As per feedback from both managers along with prospective customers, these covered concerns surrounding scalability, interoperability issues along Regulatory Compliance requirements. It was observed that rigorous research/investigation needs to explore these encounterments remedies effectively. viii The research reveals that adopting a blockchain-based software quality assurance methodology could prove invaluable towards unlocking powerful Digital Transformation benefits hidden within Tier-2 organizations trading unreservedly within autonomous vehicle systems industries displaying adherence to strict data accuracy/integrity protocols and incorporating steadfast security measures inspiring consumer confidence inevitably. The results from survey data thus provide insights heavily guiding future corporate resolution-making phases using custom-centric product management, whose outlook is geared towards promoting steady long-term growth via collaborative efforts harnessing vast software engineering expertise in dealing with autonomous vehicles within the robotaxi marketplace. Nevertheless, making headway in tackling the challenges, there were limitations identified, which are a matter of the utmost priority while executing Blockchain technology integrations into the enterprise architecture. Further research aimed at mitigating risks while optimising blockchain technology utilisation in software quality assurance initiatives involved, driving Digital Transformation may lead this research forward.